Preventive effect of curcumin and its highly bioavailable preparation on hearing loss induced by single or repeated exposure to noise: A comparative and mechanistic study - Taro Yamaguchi; Masanori Yoneyama; Yusuke Onaka; Atsushi Imaizumi; Kiyokazu Ogita (Elsevier, 2017)
We sought to determine the preventive effects of curcumin and its highly bioavailable preparation on noise-induced hearing loss in a novel murine model of permanent hearing loss developed by repeated exposure to noise. Upon exposure to noise (8-kHz octave band noise, 90 dB sound pressure level, 1 h), hearing ability was impaired in a temporary and reversible manner. During repeated noise exposure (1-h exposure per day, 5 days), there was a progressive increase in the auditory threshold shift at 12 and 20 kHz. The threshold shift persisted for at least 6 days after noise exposure. Oral administration of curcumin for 3 days before and each day during noise exposure significantly alleviated the hearing loss induced by repeated noise exposure. Curcumin abolished intranuclear translocation of nuclear factor-κB-p65 and generation of 4-hydroxynonenal-adducted proteins found in the cochlea after noise exposure. Theracurmin®, a highly absorbable and bioavailable preparation of curcumin, had strong preventive effects on hearing loss induced by repeated noise exposure. Together, these data suggest that curcumin exerts a preventive effect on noise-induced hearing loss and is therefore a good therapeutic candidate for preventing sensorineural hearing loss.